Active Compounds of Red Ginger as Antioxidant Activity in the Supplementation and Treatment of Depression - Ira Aini Dania; Rusdiana Rusdiana; Aldy S. Rambe; Urip Harahap; Elmeida Effendy; Nanda Novziransyah (Qubahan Academic Journal)
This study examined compound active of red ginger related for supplementation and treatment of depression. Depression prevalence in Indonesia from the national population survey 6.9% had severe depression symptoms, 21.8% moderate to severe. Red ginger provided gold potential and demonstrated prominent natural phenomena and coexistence, abundant benefits. Standard herbal medicine and phytopharmaceuticals as one effort in dealing with depression disorder. Problem Statement. The use of medicines for depression disorder in the long term becomes a serious problem affecting various sectors and needs to be thought of side effects and complications. Objective. Antioxidants in red ginger (Zingiber Officinale Rosc. Var Rubrum has a secondary metabolite considered for treatment or supplementation in depression disorders. This study was experimental analytical study for analyzing secondary metabolism using phytochemical screening tests and examining active compounds with the combination of liquid chromatography with tandem mass spectrometry (LCMS/MS).Red ginger extracts contain secondary metabolic flavonoids of 48.79 mgQE/g, phenol 92.73 mgGAE/G and antioxidants of 39.96 ppm. Establishment of the active compound that has an effect as an antioxidant α-Eleostearic acid (C18 H30 O2) chemspider result 10, mzcloud 96, L Histidine (C6 H9 N3 O2) chemspiders result 6, mzcloud 94,8. Tetrahydrocurcumin (C21 H24 O6) chemspider result 41, mzcloud 92,5. Active compounds of red ginger antioxidants are diarylheptanoid, phenylbutenoid, flavonoid, diterpenoide, sesquiterpenoid, gingerol and shogaol. Red ginger extract content of active flavonoid compounds and has an effect as an antioxidant is potentially used as a supplement in the treatment of depression disorders.